Politics and Remembrance : Republican Themes in Machiavelli, Burke, and Tocqueville. - Smith, Bruce James (Studies in moral, political, and legal philosophy., 2014)
This inquiry into the nature of political action concerns what the author describes as the most precarious and uncertain of human endeavors." Focusing on specific themes in Machiavelli, Burke, and Tocqueville, Bruce Smith identifies political action as a distinct mode of human activity. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.